2014
DOI: 10.1007/s10195-014-0310-2
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric medial epicondyle fractures with intra-articular elbow incarceration

Abstract: BackgroundIntra-articular incarceration of the epicondylar fragment occurs in 5–18 % of all cases of medial epicondyle fracture. It requires stable fixation to allow early motion, since elbow stiffness is the most common complication following medial epicondyle fracture. In this retrospective study, we report the clinical and functional outcomes and the complications that occurred following open reduction and screw fixation of medial epicondyle fractures with intra-articular fragment incarceration.MethodsThirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 25 publications
(35 reference statements)
5
37
0
5
Order By: Relevance
“…In their study evaluating the clinical results of 33 elbow dislocations including 30 % pure dislocations in childhood, Frongia et al [9] reported good to excellent results for all children. Excellent results were also demonstrated in patients with posterolateral dislocation associated with medial epicondyle fracture [12]. In our study, according to MEPS score, the clinical outcome was excellent in nine patients, good in two and fair in one.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In their study evaluating the clinical results of 33 elbow dislocations including 30 % pure dislocations in childhood, Frongia et al [9] reported good to excellent results for all children. Excellent results were also demonstrated in patients with posterolateral dislocation associated with medial epicondyle fracture [12]. In our study, according to MEPS score, the clinical outcome was excellent in nine patients, good in two and fair in one.…”
Section: Discussionsupporting
confidence: 52%
“…Dislocations of the elbow have been reported as often accompanied by disruption of multiple stabilisers, and thus the patho-physiology is complicated [15]. Traumatic elbow dislocation is uncommon in skeletally immature patients and generally diagnosed with concomitant fractures, avulsions or neurovascular injuries around the joint [1,5,6,[12][13][14][15][16][17][18][19]. Acute traumatic pure elbow dislocation in childhood is even more uncommon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Options for fixation include sutures, Kirschner wires (K-wires), cannulated screws, and excision of the fragment with advancement of the medial soft tissues [ [34][35][36][37] suggest the use of K-wires in younger children and cannulated screws in older children. Sutures are typically used only for very small or comminuted fragments.…”
Section: Operative Managementmentioning
confidence: 99%
“…Several authors [8 & ,19,35] report excellent Mayo Elbow Performance Scores, no deformity or valgus instability, and an average loss of 4-6.4 degrees of extension following open reduction and internal fixation of medial epicondyle fractures associated with incarceration, dislocation, or both. Furthermore, these patients can be expected to return to sports, an average 4 months postoperatively, at their preinjury level [35].…”
Section: Operative Managementmentioning
confidence: 99%